2007
DOI: 10.1002/jcb.21309
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive collagenase‐1 synthesis through MAPK pathways is mediated, in part, by endogenous IL‐1α during fibrotic repair in corneal stroma

Abstract: Collagenase-1 is a protease expressed by active fibroblasts that is involved in remodeling of the extracellular matrix (ECM). In this study, we characterize the intracellular signaling mechanism of collagenase-1 production by IL-1alpha in subcultured normal fibroblasts (NF) from uninjured normal corneas, compared to that in repair wound fibroblasts (WF). In NF, collagenase-1 was induced specifically after the exogenous addition of IL-1alpha via activation of ERK and p38MAPK. Collagenase-1 expression was strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Inhibition of JNK signaling suppressed TGF-β induced CTGF expression and scarring in penetrating corneal wounds (Shi et al, 2012). Inhibitors of mTOR and p38 MAP kinase signaling were able to markedly reduce the expression of α-SMA and collagenase in corneal cells and injured corneas (Jung et al, 2007; Huh et al, 2009; Milani et al, 2013). In alkali-burned corneas, blocking of VEGF by neutralizing antibody bevacizumab also inhibited TGF-β expression and improved corneal transparency (Lee et al, 2009).…”
Section: Corneal Stromal Wound Healingmentioning
confidence: 99%
“…Inhibition of JNK signaling suppressed TGF-β induced CTGF expression and scarring in penetrating corneal wounds (Shi et al, 2012). Inhibitors of mTOR and p38 MAP kinase signaling were able to markedly reduce the expression of α-SMA and collagenase in corneal cells and injured corneas (Jung et al, 2007; Huh et al, 2009; Milani et al, 2013). In alkali-burned corneas, blocking of VEGF by neutralizing antibody bevacizumab also inhibited TGF-β expression and improved corneal transparency (Lee et al, 2009).…”
Section: Corneal Stromal Wound Healingmentioning
confidence: 99%
“…8 MMP 2, 3, 7, 9, 12 and 13 have been identified in migrating epithelial cells, stromal keratocytes and inflammatory cells. 7,[13][14][15][16][17][18] MMP14 expression was strongly induced in basal epithelial cells in the initial days after corneal wounding, appearing later in keratocytes. 17 It has been suggested that MMP14 has a role in stromal extracellular matrix remodeling 17 but no report thus far has attempted to modulate its expression in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…2,[15][16][17][18] The cornea has been an important experimental model for defining mechanisms of MMP expression and role in normal and pathologic repair processes, including epithelial regeneration and failure to heal, fibrotic repair and scar remodeling, infection, and angiogenesis. 2,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] These studies have revealed that specific MMPs appear in specific locations in the repairing cornea correlated with events occurring on the cellular and tissue level. For example, MMP-9 is produced in the corneal epithelium regenerating across the intact basement membrane after abrasion injury and then disappears once regeneration is complete.…”
mentioning
confidence: 99%